Genomic Analysis of Caenorhabditis elegans Reveals Ancient Families of Retroviral-like Elements - Bowen, Nathan J.; McDonald, John F. (Genome Research, 1999)
Retrotransposons are the most abundant and widespread class of eukaryotic transposable elements. The recent genome sequencing ofCaenorhabditis elegans has provided an unprecedented opportunity to analyze the evolutionary relationships among the entire complement of retrotransposons within a multicellular eukaryotic organism. In this article we report the results of an analysis of retroviral-like long terminal repeat retrotransposons in C. elegans that indicate that this class of elements may be even more abundant and divergent than previously expected. The unexpected presence, in C. elegans, of an element displaying a number of characteristics previously thought to be unique to vertebrate retroviruses suggests an ancient lineage for this important class of infectious agents.